Cameroon Economic Update, July 2011, Issue No. 2 : Towards Better Service Delivery - World Bank (Washington, DC, 2017)
These economic updates analyze the trends and constraints in Cameroon's economic development. Each issue, produced bi-annually, provides an update of recent economic developments as well as a special focus on a selected topical issue. The economic updates aim to share knowledge and stimulate debate among those interested in improving the economic management of Cameroon and unleashing its enormous potential. The notes thereby offer another voice on economic issues in Cameroon, and an additional platform for engagement, learning and change. The latest information confirms the expected recovery in economic activity in Cameroon. The upturn in the global economy and measures taken by the authorities to stimulate domestic production, real gross domestic product (GDP) growth in 2010 is estimated to have reached 3.2 percent (compared to 2 percent in 2009). As expected, most of this recovery was driven by the tertiary sector, which accounted for more than half of the estimated growth. The sector benefitted from a pick-up in timber-related transport and continued strong activities in mobile telephony stemming from a greater use of fiber optic, promotional campaigns during the Soccer World Cup, and the roll-out of new products. The recovery in the primary sector, with an estimated growth rate of about 4 percent in 2010, was led by a strong expansion in the timber sector, as well as in food crops. The non-oil secondary sector, meanwhile, is also estimated to have grown by about 4 percent, driven by a continued pick-up in construction activities and a rebound in food processing. Cameroon is a relatively small and mature oil producer, where oil production is declining. Depleting reserves, aging equipment, and more recently postponements of some development projects and investments because of the financial crisis explain this profile. The contribution of this sector to GDP growth has been mostly negative in recent years and oil production is estimated to have contracted by a further 12 percent in 2010 (to 23.2 million barrels).